Humanized childbirth: an integrative review (Research, Society and Development, 2021)
Objective: Assess and identify the main difficulties encountered during care delivery to parturients and present continuing education methodologies. Methods: Integrative review study, seeking to analyze scientific studies on the perception of nursing in humanized care. Results: Created a summary table containing 23 articles to be analyzed; 09 of them analyzed the importance of preparing the woman from the beginning of pregnancy. 03 in order to assess the knowledge of technical and scientific nurses adequate for care. 05 with regard to linking knowledge, improve the quality of humanized care by the nursing team, including women. 06 As a suggestion for continuing education and professional training. Conclusion: to minimize the mistakes made during the performance and ensure the success of qualified assistance from the team, it depends on several individual and collective factors. The nurse, as the main manager of each unit, must be concerned with establishing continuing education for their team, implementing assistance protocols for humanized care, and performing the role of continuous supervisor.